Study on assessment of slope stability and mixed disposal of overburden in voids of Singrauli Coalfield - Shirin, S; Jamal, A; Ranjan, P.; Yadav, A.K. (John Wiley and Sons Inc., 2019)
The mining industry can be considered the backbone of the Indian economy as well as facilitating the power that drives most of the other industries in the company. The overburden and waste rocks produced during coal mining are major concerns in regard to the amount of land that is required for their disposal, as well as the stability of dumps for these materials, which are of increasing height. Land reclamation issues are also a concern. In this work the adverse impacts caused by the dumping of overburden on land and acidic mine water on water bodies is discussed. Remote sensing tools were used along with the laboratory experimentation to assess the various impacts. This study also shows that silt released from waste dumps, can affected the angle of repose of the overburden dump slope. The angle of repose of the overburden materials varies with particle size composition. Thus, use of in-pit crushers in large opencast mining operations can effectively reduce the area locked under the waste dumps. The acid neutralization potential of fly ash and overburden for the treatment of acid water was tested in the laboratory by using fly ash and waste rock materials on acidic coalfield water. The results are encouraging, and fly ash may prove to be a good acid neutralizer when used in conjunction of coal overburden material. © 2019 Wiley Periodicals, Inc.
Keywords: acidic mine water,fly ash,overburden materials,slope stability and opencast mines